An N-heterocyclic carbene iridium(III) complex as a potent anti-cancer stem cell therapeutic. (1st November 2022) - McCartin, Conor; Mathieu, Eric; Dontenwill, Monique; Herold-Mende, Christel; Idbaih, Ahmed; Bonfiglio, Anna; Mauro, Matteo; Fournel, Sylvie; Kichler, Antoine
Abstract: Cancer stem cells (CSCs) represent a difficult to treat cellular niche within tumours due to their unique characteristics, which give them a high propensity for resistance to classical anti-cancer treatments and the ability to repopulate the tumour mass. An attribute that may be implicated in the high rates of recurrence of certain tumours. However, other characteristics specific to these cells, such as their high dependence on mitochondria, may be exploited for the development of new therapeutic agents that are effective against the niche. As such, a previously described phosphorescent N-heterocyclic carbene iridium(III) compound which showed a high level of cytotoxicity against classical tumour cell lines with mitochondria-specific effects was studied for its potential against CSCs. The results showed a significantly higher level of activity against several CSC lines compared to non-CSCs. Mitochondrial localisation and superoxide production were confirmed. Although the cell death involved caspase activation, their role in cell death was not definitive, with a potential implication of other, non-apoptotic pathways shown. A cytostatic effect of the compound was also displayed at low mortality doses. This study thus provides important insights into the mechanisms and the potential for this class of molecule in the domain of anti-CSC therapeutics. Graphical abstract: Image 1 Highlights: An NHC–Ir(III) compound shows a high level of toxicity against cancer stem cells. NHC–Ir(III) shows mitochondrial localisation and superoxide production. NHC–Ir(III) induces caspase activation, but inhibition does not reduce cell death. The cell death mode presents a necrosis-like morphology. NHC–Ir(III)'s mode of action includes a potent cytostatic effect.